1999
DOI: 10.1029/1999jd900256
|View full text |Cite
|
Sign up to set email alerts
|

Simulating midsummer climate over southern Africa using a nested regional climate model

Abstract: Abstract. The Commonwealth Scientific and Industrial Research Organisation (CSIRO)Division of Atmospheric Research limited area model (DARLAM) is used to simulate midsummer (January) climate over southern Africa. Using a one-way nesting procedure, lateral boundary and initial conditions are supplied by the CSIRO nine-level Mark 2 general circulation model (GCM), CSIRO9. In general, the DARLAM results are improved in comparison with those from CSIRO9, although certain deficiencies in the GCM climatology over so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This is an important outcome of the present study since some of the previous studies (Joubert et al 1999;Engelbrecht et al 2002;Hudson and Jones 2002;Boulard et al 2012) had difficulties to reproduce the observed ENSO-southern Africa rainfall relationship in their regional climate modeling experiments. The present study has successfully reproduced the strength of observed ENSO-South Africa rainfall relationship over the period Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is an important outcome of the present study since some of the previous studies (Joubert et al 1999;Engelbrecht et al 2002;Hudson and Jones 2002;Boulard et al 2012) had difficulties to reproduce the observed ENSO-southern Africa rainfall relationship in their regional climate modeling experiments. The present study has successfully reproduced the strength of observed ENSO-South Africa rainfall relationship over the period Fig.…”
Section: Discussionmentioning
confidence: 78%
“…RCMs have previously been used as dynamical downscaling aids for studying regional climates over southern Africa (Joubert et al 1999;Engelbrecht et al 2002;Hud-son and Jones 2002;Tadross et al 2006;Kgatuke et al 2008;Landman et al 2009). The weather research and forecasting (WRF) model (Skamarock et al 2008) is increasingly being used as RCM for downscaling studies over southern Africa (Cre´tat et al 2011(Cre´tat et al , 2012Ratnam et al 2012Ratnam et al , 2013Cre´tat and Pohl 2012;Boulard et al 2012;Vigaud et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the most suitable domain, physical parameterizations and lower boundary conditions, a multi-year integration is required in order to properly recognize anomalous behaviour relative to the regional model's time-averaged behaviour (Goddard et al, 2001), which requires a large amount of computer time and storage space. However, nested modelling approaches are capable of simulating the details of regional climate over southern Africa with greater skill than global models (Joubert et al, 1999). Owing to the large expense involved when using a combination of GCMs and regional models and to a lesser extent a combination of GCMs and empirical downscaling methods, the GCM-based approaches to seasonal rainfall estimation should produce rainfall forecasts with skill that outscores that of simple empirical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…As examples, some of the papers that address climate variability, and related topics of different regions, are provided as examples here; a few of these papers also study the climate change scenarios, along with present day climate simulations as control. These are, over the United States (Dickinson et al 1989;Giorgi 1990;Giorgi et al 1994;Dai et al 1999), Australia (McGregor andWalsh 1993, 1994;Walsh and McGregor 1995), New Zealand (Renwick et al 1998), Europe (Giorgi et al 1990;Marinucci 1996a, 1996b), south Africa (Joubert et al 1999), south America (Nicolini et al 2002;Misra et al 2002), east Asia (Kida et al 1991;Liu et al 1994;Hirakuchi and Giorgi 1995;Sasaki et al 1995;Fukutome et al 1999;Kato et al 1999;Leung et al 1999;Kato et al 2001;Mabuchi et al 2000), China (Zheng et al 2002;Liu et al 2003;Wang et al 2003), east Africa (Sun et al 1999a(Sun et al , 1999b and India (Bhaskaran et al 1996(Bhaskaran et al , 1998Bhaskar Rao et al 2001) etc. Several studies suggest that the finer features of the regional climate are better simulated by the regional climate models, as compared to those by GCMs or reanalysis.…”
Section: Introductionmentioning
confidence: 99%